Anisotropic lattice expansion determined during flash sintering of BiFeO3 by in-situ energy-dispersive X-ray diffraction. (15th March 2019) - Wassel, Mary Anne B.; Pérez-Maqueda, Luis A.; Gil-Gonzalez, Eva; Charalambous, Harry; Perejon, Antonio; Jha, Shikhar K.; Okasinski, John; Tsakalakos, Thomas
Abstract: BiFeO3 has a Curie temperature (TC ) of 825 °C, making it difficult to sinter using conventional methods while maintaining the purity of the material, as unavoidably secondary phases appear at temperatures above Tc . Flash sintering is a relatively new technique that saves time and energy compared to other sintering methods. BiFeO3 was flash sintered at 500 °C to achieve 90% densification. In-situ energy dispersive X-ray diffraction (EDXRD) revealed that the material did not undergo any phase transformation, having been sintered well below the TC . Interestingly, anisotropic lattice expansion in the material was observed when the sample was exposed to the electric field. Graphical abstract: Unlabelled Image